Influence of platform switching on crestal bone changes at nonsubmerged titanium implants: a histomorphometrical study in dogs - Ju¨rgen Becker (Blackwell Synergy, 2007)
Objectives: The aim of the present study was to investigate histomorphometrically the influence of platform switching on crestal bone changes at non-submerged wide-body titanium implants in a dog model. Material and Methods: One-stage insertion of sand-blasted and acid-etched screw-type implants with either matching (CAM) or smaller-diameter healing abutments (CPS) were randomly assigned to the lower jaws of nine beagle dogs. The animals were killed after 7, 14, and 28 days of non-submerged healing. Dissected blocks were processed for histomorphometrical analysis. Measurements were made between the implant shoulder (IS) and: – the apical extension of the long junctional epithelium (aJE), – the most coronal level of bone in contact with the implant (CLB), and – the level of the alveolar bone crest (BC). Results: At 7, 14, and 28 days, the mean IS–aJE values were significantly the lowest at CPS implants. However, after 28 days of healing, both groups revealed significantly increased mean IS–BC values at the buccal aspect of the alveolar bone. The difference in IS–CLB and IS–BC between groups was not significant. Conclusions: Within the limits of the present study, it was concluded that both CAM and CPS implants revealed crestal bone-level changes after 28 days of healing.